The Association of COL1A2 rs17166249 and rs412777 Polymorphisms on the Bone Mineral Density in Polish Postmenopausal Women - Adam Kamiński; Mateusz Gutowski; Anna Bogacz; Marta Podralska; Izabela Uzar; Michał Soczawa; Maciej Brązert; Bogusław Czerny (Biomolecules, 2025)
Background: Osteoporosis is a chronic metabolic condition characterized by progressive loss of bone mass and disruption of the bone spatial architecture. Pathological changes are influenced by multiple factors, including genetic predispositions. Identifying risk factors for osteoporosis is crucial for recognizing at-risk populations, implementing preventive strategies, and supporting diagnostics. Type I collagen, composed of two chains—α1(I) and α2(I), encoded by the COL1A1 and COL1A2 genes, respectively—plays a key role in the mechanical strength of tissues, including bones. The aim of this study was to assess the effect of the rs17166249 and rs412777 polymorphisms in the COL1A2 gene on bone mineral density (BMD) in postmenopausal women. Methods: The study included 570 unrelated women: 119 diagnosed with osteoporosis, 96 with osteopenia, and 355 healthy controls. Polymorphisms in the COL1A2 gene were analyzed using real-time PCR with specific primers and TaqMan probes. Results: The results showed no significant differences in the distribution of genotypes and alleles of rs412777 between the groups. However, the rs17166249 T allele was found to be more prevalent in the osteoporosis group, although the association was not statistically significant after adjusting for confounders. Furthermore, no significant correlations were observed between the genotypes of either SNP and BMD parameters such as T-score, Z-score, and BMD measurements. Conclusion: These findings suggest that while the COL1A2 gene may have a modest influence on bone health, its role in osteoporosis risk remains inconclusive, highlighting the need for further studies to explore additional genetic and environmental factors.